2022
DOI: 10.1155/2022/6409346
|View full text |Cite
|
Sign up to set email alerts
|

Exosome Derived from Human Neural Stem Cells Improves Motor Activity and Neurogenesis in a Traumatic Brain Injury Model

Abstract: Traumatic brain injury (TBI) is a leading cause of mortality and long-lasting disability globally. Although novel treatment options have been investigated, no effective therapeutic opportunities for TBI exist. Accumulating studies demonstrated that the paracrine mechanisms of stem cells may allow them to orchestrate regenerative processes after TBI. So far, very little attention has been paid to the beneficial effects of human neural stem cells (hNSCs) in comparison to their exosomes as a paracrine mechanism. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…The mNSS neurological function assessment at day 7 after TBI, a total of 15 studies were eligible ( Zhang et al, 2015 , 2017 , 2020 ; Li et al, 2019 ; Ni et al, 2019 ; Yang et al, 2019 ; Chen et al, 2020 ; Long et al, 2020 ; Xu et al, 2020 ; He et al, 2021 ; Zhang W. et al, 2021 ; Zhang Y. et al, 2021 ; Abedi et al, 2022 ; Cui et al, 2022 ; Zhang et al, 2022 ). The network diagram ( Figure 4A ) showed four interventions and control comparisons, including AEVs, MEVs, neural stem cell-derived extracellular vesicles (NSCEVs) and MSCEVs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mNSS neurological function assessment at day 7 after TBI, a total of 15 studies were eligible ( Zhang et al, 2015 , 2017 , 2020 ; Li et al, 2019 ; Ni et al, 2019 ; Yang et al, 2019 ; Chen et al, 2020 ; Long et al, 2020 ; Xu et al, 2020 ; He et al, 2021 ; Zhang W. et al, 2021 ; Zhang Y. et al, 2021 ; Abedi et al, 2022 ; Cui et al, 2022 ; Zhang et al, 2022 ). The network diagram ( Figure 4A ) showed four interventions and control comparisons, including AEVs, MEVs, neural stem cell-derived extracellular vesicles (NSCEVs) and MSCEVs.…”
Section: Resultsmentioning
confidence: 99%
“…The mNSS neurological function assessment at day 14 after TBI, a total of 14 studies were eligible (Zhang et al, 2015(Zhang et al, , 2017(Zhang et al, , 2020Li et al, 2019;Ni et al, 2019;Yang et al, 2019;Chen et al, 2020;Long et al, 2020;Xu et al, 2020;He et al, 2021;Zhang Y. et al, 2021;Abedi et al, 2022;Cui et al, 2022;. The network diagram (Figure 5A (87.12%).…”
Section: Comparison Of the Efficacy Of Evs From Different Cell Source...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of TBI, the secretome of MSC has the capacity to enhance endogenous neurogenesis (Liu et al, 2020;Badner and Cummings, 2022). Porcine and rodent models show that extracellular vesicles released by MSC can promote endogenous angiogenesis and neurogenesis, reduce inflammation, and facilitate cognitive and sensorimotor recovery after TBI (Abedi et al, 2022;Bambakidis et al, 2022). This highlights the significance of the trophic support these cells provide during exogenous application (Spees et al, 2016;Liu et al, 2020).…”
Section: Stem Cellsmentioning
confidence: 99%
“…In recent years, EV‐based stem cell‐free therapies have been investigated in the course of TBI treatment. Abedi et al 165 . reported that administration of NSC‐EVs improved recent‐period neurological behaviors and promoted neurogenesis after TBI.…”
Section: Application Of Nsc‐evs In Neurological Diseases and Other Di...mentioning
confidence: 99%